RELATION OF EDUCATION LEVEL AND KNOWLEDGE ON MOTIVATION IN DOING GYMNASTICS IN THIRD TRIMESTER PREGNANT WOMAN IN BENGKULU CITY - M. Wisnu Age Prayoga (Sriwijaya University Learning and Education International Conference, 2018)
The purpose of this study was to analyze the correlation between education and knowledge level on motivation in doing gymnastics in third trimester pregnant women in Bengkulu city. The method used in this study is cross-sectional, because researchers do observation or measurement of variables with the approach at once at one time. The population used were all pregnant women of third trimester at 5 public health centers of Bengkulu city, amounting to 107 pregnant women. Data collection techniques in this study is a questionnaire (questionnaire) by conducting tests before and after applied knowledge about pregnancy exercise. Technique of data analysis in this research use chi square test. Based on the output using computerized system program spss version 16 for windows with a significant level of small p of 0.05 that the value of education level is 0.751 and the value of knowledge is 0.671. Based on the results of this study, it can be concluded that there is no relationship between the level of education and knowledge of motivation in doing gymnastics in third trimester pregnant women in the city of Bengkulu because more than the standard value of chi square is 0.05. It is recommended to connect in the form of other variations to be more easily applied to pregnant women third trimester.